2005
DOI: 10.1038/sj.onc.1208417
|View full text |Cite
|
Sign up to set email alerts
|

Human Cripto-1 overexpression in the mouse mammary gland results in the development of hyperplasia and adenocarcinoma

Abstract: Human Cripto-1 (CR-1) is overexpressed in approximately 80% of human breast, colon and lung carcinomas. Mouse Cr-1 upregulation is also observed in a number of transgenic (Tg) mouse mammary tumors. To determine whether CR-1 can alter mammary gland development and/or may contribute to tumorigenesis in vivo, we have generated Tg mouse lines that express human CR-1 under the transcriptional control of the mouse mammary tumor virus (MMTV). Stable Tg MMTV/CR-1 FVB/N lines expressing different levels of CR-1 were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 72 publications
(76 reference statements)
2
67
0
1
Order By: Relevance
“…The overexpression of Cripto-1 induces transformation and enhances cell motility and branching morphogenesis in mouse mammary epithelial cells in vitro (15,16). Our data show for the first time that Cripto-1 expression is elevated in tumor promoter -treated skin and chemically induced mouse skin papillomas.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The overexpression of Cripto-1 induces transformation and enhances cell motility and branching morphogenesis in mouse mammary epithelial cells in vitro (15,16). Our data show for the first time that Cripto-1 expression is elevated in tumor promoter -treated skin and chemically induced mouse skin papillomas.…”
Section: Discussionmentioning
confidence: 52%
“…Overexpression of Cripto-1 increases cell proliferation, anchorage-independent growth, and transformation of mammary epithelial cells in vitro and causes mammary gland hyperplasia and tumor formation in transgenic MMTV-Cripto-1 mice (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…In the MMTV-CR-1 transgenic mouse model, overexpression of Cripto-1 was associated with significantly increased lateral side branching of the developing mammary ducts [82]. In another transgenic model where Cripto-1 expression was driven by the Whey acidic protein promoter, the mammary glands of the transgenic mice overexpressing Cripto-1 were characterized by delayed lobuloalveolar development [83] (Fig.…”
Section: Cripto-1 and Nodal During Mammary Gland Development And Tumomentioning
confidence: 99%
“…[25][26][27] Furthermore, transgenic mouse models have demonstrated that overexpression of a human CR-1 transgene in the mammary gland under the control of the mouse mammary tumor virus (MMTV) or the whey acidic protein promoter results in multifocal mammary hyperplasias and adenocarcinomas in approximately 30 to 50% of multiparous mice. 28,29 MMTV-CR-1 mice have also been recently shown to develop uterine leiomyosarcomas. 30 The presence of a GPI anchor in the mouse and human Cripto-1 protein suggests that this molecule might localize to lipid rafts, which are cell membrane regions that function as microdomains for a number of signaling molecules that are GPI-linked.…”
mentioning
confidence: 99%